Communicative Specificity of the First National Printed Newspaper “Peter the Great’s Vedomosti” - I. Yu. Kuksa (Научный диалог, 2019)
The main communicative characteristics of the first printed Russian newspaper, “Peter the Great’s Vedomosti” are discussed in the article. It briefly indicates the historical context of the appearance of the first national print edition, determines the sociocultural and functional significance of the newspaper, its type as a publication, including comparison with the predecessor “Vedomosti”, the first handwritten newspaper “Vesti Kuranty”, which status is still debatable. The main communicative parameters of the newspaper are qualified: the goal, objectives, features of the addressant and the addressee, as well as news reports in the context of the birth of national journalism. Such important for periodicals characteristics, as efficiency and information needs of the readership are commented. The problem of the authorship of the newspaper news text in this historical period is discussed. The structural complexity and different functional roles of the newspaper texts creators, as well as the way the author introduces new information, including the emergence of a news note model is emphasized. It reveals the communicative position of the author of the newspaper text in terms of the space-time approach and the means of its representation. The thematic range of newspaper materials placed in the set of “Peter the Great’s Vedomosti” for 1710 is determined, a qualitative and quantitative characteristic of thematic groups is given.